AJM300, a novel oral antagonist of α4‐integrin, sustains an increase in circulating lymphocytes: A randomised controlled trial in healthy male subjects. Issue 3 (28th January 2020) - Fukase, Hiroyuki; Kajioka, Toshifumi; Oikawa, Ichiro; Ikeda, Naoki; Furuie, Hidetoshi
Abstract : Aims: AJM300 is an oral antagonist of α4‐integrin that reduces inflammation by blocking leucocyte trafficking. This study aimed to investigate safety, tolerability, pharmacokinetics and pharmacodynamics of AJM300 in healthy male subjects. Methods: A total of 23 subjects were randomised to receive 240 mg ( n = 6), 480 mg ( n = 5), 960 mg ( n = 6) of AJM300 or the corresponding placebo ( n = 2 per group). The study drugs were taken orally 3 times daily after each meal on the first day followed by a 4‐day washout period. Thereafter, multiple‐dose administration was conducted for 6 consecutive days. The pharmacokinetic parameters of AJM300 and its active metabolite (HCA2969) were assessed, and total white blood cells and the differential cell count were used to determine the pharmacodynamic effects. Adverse events (AEs) were also monitored. Results: The plasma AJM300 and HCA2969 concentration–time curves displayed a triphasic pattern on Day 1 (single‐day administration) and Day 10 (last day of multiple dosing), whereas the concentration of HCA2969 was much higher than that of AJM300. A significant but transient increase in lymphocyte count was observed after AJM300 dosing at all dosages tested compared with the placebo. The increase was sustained over a 24‐h period only at the 960‐mg dosage. In particular, a significant increase in the lymphocyte count compared to placebo (mean, 50.58%; 95% confidence intervals, 20.40–80.76) was observed at the first 960‐mg dose on Day 10. Six (26.1%) subjects reported ≥1 AEs, all of which were mild and resolved spontaneously. Conclusion: The maximal and 24‐h sustained pharmacodynamic effects were demonstrated at the 960‐mg dosage after oral administration of AJM300 3 times daily for 6 days, which was also found to be safe and well tolerated.